Cognitive abilities and behavioral biases - Oechssler, Joerg; Roider, Andreas; Schmitz, Patrick W. (Journal of economic behavior & organization, 2009)
We use a simple, three-item test for cognitive abilities to investigate whether established behavioral biases that play a prominent role in behavioral economics and finance are related to cognitive abilities. We find that higher test scores on the cognitive reflection test of Frederick [Frederick, S., 2005. Cognitive reflection and decision-making. Journal of Economic Perspectives 19, 25-42] indeed are correlated with lower incidences of the conjunction fallacy and conservatism in updating probabilities. Test scores are also significantly related to subjects’ time and risk preferences. Test scores have no influence on the amount of anchoring, although there is evidence of anchoring among all subjects. Even if incidences of most biases are lower for people with higher cognitive abilities, they still remain substantial.